Eksistensi Interaksi Simbolik Kebudayaan Jual Beli Ternak Marosok di Payakumbuh Sumatra Barat - Putri, Aini Eka; Banowo, Emilianshah (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Globalization and technological advancements often change the patterns of symbolic interaction, especially in the culture of livestock trading through "marosok" in Payakumbuh, West Sumatra. The purpose of this research is to understand the symbolic interaction in the culture of livestock trading through "marosok" in Payakumbuh, West Sumatra, to recognize the significance of the culture of buying and selling cattle in Payakumbuh, West Sumatra, and to determine the existence of the culture of livestock trading through "marosok" in Payakumbuh, West Sumatra. The theory employed in this research is symbolic interaction theory, which focuses on the relationship between humans and symbolic meanings, as proposed by George Herbert Mead, comprising three key concepts: Self, Mind, and Society. The research methodology employed in this study is qualitative descriptive research with an ethnographic approach. The findings of this research indicate th at the culture of buying and selling livestock through "marosok" is still practiced by the community and remains existent among livestock traders. However, many members of the community are aware of the practice but do not fully understand the symbols associated with "marosok." Technologicaladvancements have facilitated the spread of this cultural practice and have not posed a threat, providing a means for the community to promote livestock. There are numerous positive values associated with this culture, including tranquility and the absence of envy or rivalry among traders. As a result, the culture of buying and selling livestock through "marosok" continues to thrive. The local community is making efforts to preserve this cultural tradition by raising awareness among the local population about the importance of "marosok" and persuading them to support it, even if the scope is limited to the family environment. ABSTRAK Globalisasi dan kemajuan teknologi sering mengubah cara pada pola interaksi simbolik khususnya pada kebudayaan jual beli ternak dengan cara marosok , Tujuan penelitian ini adalah mengetahui interaksi simbolik kebudayaan jual beli ternak marosok di Payakumbuh Sumatra Barat, mengetahui penting kebudayaan jual beli ternak sapi dan kerbau di Payakumbuh Sumatra Barat, serta ingin mengetahui eksistensi kebudayaan jual beli ternak marosok di Payakumbuh Sumatra Barat. Teori yang digunakan pada penelitian ini adalah teori interaksi simbolik. Teori interaksi simbolik adalah hubungan manusia dengan makna simbol, menurut George Herbert Mead yang terdiri dari tiga konsep diantaranya Self (diri sendiri), Mind (pikiran), dan Society atau masyarakat. Metode yang digunakan dalam penelitian ini adalah metode deskripti kualitatif dengan pedekatan etnografi. Hasil penelitian ini adalah kebudayaan jual beli dengan cara marosok masih dijalankan oleh masyarakat dan tetap eksis dikalangan pedagang ternak namun kebanyakan dari masyarakat hanya mengetahui tetapi tidak mengerti akan simbol-simbol pada marosok. Perkembangan teknologi membantu menyebarluaskan kebudayaan jual beli ternak marosok tidak menjadi sebuah ancaman dan menjadi pilihan bagi masyarakat untuk mempromosikan hewan ternak. Banyak terdapat nilai-nilai positif dalam kebudayaan ini diantaranya ketentraman dan tidak menimbulkan saling dengki ataupun iri terhadap pendagang lain. Sehingga kebudayaan jual beli ternak dengan marosok sampai saat ini masih terus dilaksanakan. Upaya masyarakat dalam melestarikan kebudayaan marosok dengan memberikan kesedaran kepada masyarakat setempat tentang pentingnya kebudayaan jual beli ternak dengan cara marosok serta mepersuasi walaupun cakupannya kecil yaitu lingkungan keluarga. Kata Kunci: Budaya, Interaksi Simbolik, Kebudayaan Marosok